A COMPARISON OF THE PLOT IN THREE VERSIONS OF CINDERELLA MOVIES - Ong, Melisa; Sogimin, Sogimin (LINGUAMEDIA Journal, 2024)
Literature is not only in written form such as poetry, novels, short stories, and even dramas. Technological advances have made literature presented in a more modern form, namely movies. The title of this research is A Comparison of the Plot in Three Versions of Cinderella.  in Cinderella 1950 by Charles Perrault, Cinderella 2015 by Chris Weitz, And the Cinderella 2021 by Kay Cannon. This research uses objective theory to compare the three versions of Cinderella, especially in comparing plots in stories. The researcher uses qualitative descriptive to compare these movies. In collecting data. What is a limitation in analyzing this research is the plot elements which consist of six structures; exposition, inciting incident, rising action, climax, falling action, resolution or denouement. The results, through differences in plot, also produce differences in several storylines supported by the characters. This analysis is not a way to point out the weakness and weakness of each version of the movies. However, everyone sees that literature also influences and adapts to current developments. Keywords: Cinderella, Comparison, Literature, Movies, Pot.